Analysis of the development and potential of wind energy in Peru - Gordillo Valdez, Andrés (2022)
This study presents an analysis of the potential for wind energy development in Peru based on a systematic review of the research carried out in recent years, considering various variables and pertinent indicators. The research was exploratory and explanatory, with a qualitative and non-experimental approach. Among the main results of the investigation, a significant number of awarded projects and wind farms in execution in Peru were found. Likewise, it was possible to identify the amount of energy produced and that can be produced from these projects, the average price of the power generated, and the areas suitable for development, among others. All this shows that Peru is a country where wind energy is in the process of development, but its potential is not related to the development achieved today.